Fostering Organizational Citizenship Behavior Among Employees in the Indonesian Retail Industry: The Role of Transformational Leadership and Perceived Organizational Support Mediated by Work Environment - Sarwono, Tomy; Supriadi, Yudi Nur; Levianto, Jubei; Yulivan, Ivan (Yayasan Sinergi Kawula Muda, 2026)
The modern retail industry in Depok City is experiencing major challenges driven by shifting consumer behavior, rapid technological change, and the lasting effects of the COVID-19 pandemic. This study examines how Transformational Leadership (TL) and Perceived Organizational Support (POS) influence Organizational Citizenship Behavior (OCB), with Leader–Member Exchange (LMX) as a mediating variable. Using a quantitative survey of modern retail employees in Depok, the findings reveal that TL positively affects OCB, while POS influences OCB indirectly through LMX. These results highlight the importance of effective leadership and perceived support in fostering employees’ extra-role behavior within Indonesia’s retail sector. The study contributes practical insights for improving employee engagement and productivity in a post-pandemic retail environment.